Educational Thought of Imam Badr Al-Din Bin Jama`ah - Budi Marta Saudin (LP2M IAIN Ambon, 2022)
The progress of a nation depends on its educational thinking based on the direction of scholars and thinkers, and from it the goals, objectives, principles and means of education achieve goals. The Islamic ummah is the best ummah, because it is the ummah that Allah glorified with the Qur'an and the Sunnah of the Prophet Muhammad SAW and divided by the most just and straight sharia. Its history has been traversed by the role of prominent Muslim scholars who are considered as beacons in education. There is no doubt, that there are examples of thinkers and scholars who have succeeded in his life, and achieved great goals whose influence still lingers after his death, even after hundreds of years have passed. The character that the author raises in this paper in the role of Islamic education is Imam Badr al-Din bin Jama`ah. Among those who are known are because of his great interest in Islamic education and literature, he classifies and compiles, and bases his thoughts on education which is one of the foundations of Islam. Ibnu Jamaah realizes that the teacher is the most important element in the success of the educational process. The teacher education method is to read, read, study, learn, memorize, and spend time with the teacher. Ibn Jama'ah saw that a good teacher can stay away from lust in dealing with students. Abstrak: Kemajuan suatu bangsa tergantung pada pemikiran pendidikannya berdasarkan arahan dari para cendekiawan dan pemikir, dan darinya tujuan, sasaran, prinsip, dan sarana pendidikan dijabarkan. Umat Islam adalah umat yang terbaik, karena ia adalah umat yang dimuliakan Allah dengan al-Qur'an dan Sunnah Nabi Muhammad, SAW dan dikhususkan dengan syariah yang paling adil dan lurus. Sejarahnya telah dilewati dengan peran para cendekiawan muslim terkemuka yang dianggap sebagai mercusuar dalam pendidikan. Tidak diragukan lagi, bahwa ada contoh para pemikir dan ulama yang telah berhasil dalam hidupnya, dan mencapai tujuan-tujuan besar yang pengaruhnya masih ada setelah wafatnya, bahkan setelah ratusan tahun telah berlalu. Tokoh yang penulis angkat pada tulisan ini dalam peran pendidikan islam, adalah Imam Badr al-Din bin Jama`ah. Di antara yang dikenal adalah karena minatnya yang besar dalam pendidikan dan sastra Islam, ia mengklasifikasikan serta menyusun, dan mendasarkan pemikiran dalam ilmu pendidikan yang merupakan salah satu fondasi Islam. Ibnu Jamaah menyadari bahwa guru merupakan unsur terpenting dalam keberhasilan proses pendidikan. Metode pendidikan guru adalah dengan membaca, membaca, meneliti, menelaah, menghafal, dan lamanya berkumpul dengan guru. Ibnu Jama`ah melihat bahwa seorang guru yang baik dapat menjauhkan diri dari hawa nafsu dalam menghadapi siswa.